PENDIDIKAN FORMAL BERKARAKTER MULIA SEBAGAI PEMBENTUK SDM UNGGUL BERMARTABAT - I G Agung Jaya Suryawan (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Good behavior will be able to avoid bad behavior in everyday life. Someone to be able to behave well requires education, habituation, and example. Because basically the attitudes and behavior of individuals tend to imitate the behavior of others who are considered good. This imitation habit requires education, habituation, and example from those around him. This would be appropriate if done at school because school is a place to socialize and find individual identity. Learning carried out in schools in the context of building individual character is very effective if it is integrated with character education with the subjects being taught. Schools as educational units have a very heavy burden and responsibility, namely to prepare students who have good character and make human resources (HR) which are expected to support national development. Therefore, what is needed is education that is able to integrate with the development of all dimensions of human life, namely cognitive, physical, socio-emotional, creativity, and spiritual learners .keywords: Education, noble character